Pengaruh Current Ratio, Debt To Equity Ratio Dan Return On Equity Terhadap Price Earning Ratio Dengan Price To Book Value Sebagai Variabel Intervening - Putri Ismayana; Widia Astuty; Muis Fauzi Rambe (CERED Indonesia Institute, 2021)
The purpose of this study was to determine the effect of current ratio, debt to equity ratio and return on equity to price earning ratio with price to book value as an intervening variable in automotive sub-sector companies and components listed on the Indonesia Stock Exchange.. The test using path analysis proves that Price to book value can be a variable that mediates between the variable current ratio to the price earning ratio with a value of -1.278, the price to book value can be a variable that mediates between the variable debt to equity ratio to the price earning ratio with the value - 216.22 and price to book value cannot be the variables that mediate between the variable return on equity to the price earning ratio with a value of -12.847.